Atribut Kualitas Audit di Indonesia: Perspektif Penyaji dan Pengguna Laporan Keuangan Samirah Dunakhir - Samirah Dunakhir (Accounthink, 2016)
The project aims to investigate the attributes of audit quality in Indonesia by considering input from groups of audit clients and external statement users. Beside the facts of the important to consider the issue from different groups of stakeholders such as audit committee chairpersons and loan officers, there have been very few published empirical studies of perceived audit quality in Indonesia from those groups’ perspectives. This study attempts to address the gap by identifying the major attributes that enter into the determination of audit quality in Indonesia based on the perspectives of different groups of clients and external users. Survey questionnaires are sent to a random sample of the two groups. The result shows that there are significant difference perceptions between the groups.